Fundos patrimoniais endowment: nova possibilidade de financiamento para atividades dos alunos dos cursos de Economia da UFC - Leandro, Ruan Charles Ferreira (2021)
This study aimed to outline an Endowment fund to fundraise resources for the Economics Department of the Federal University of Ceará. For this research, a questionnaire was carried out with undergraduate, graduate and former students, as well as with other individuals who wish to contribute to the development of the patrimonial fund. To predict the potential fundraising power of the academic center, it was used the Contingent Valuation Method (CVM), and thus was found, The Willingness to Pay (WTP) of the interviewees. The supplementation of resources, through the incentive of civil society, will be a new tool to democratize education, financially support students who are in a situation of socioeconomic vulnerability, contribute to the modernization of the institution's infrastructure, support teaching, research and extension in general.